Money Demand: The Effects of Inflation and Alternative Adjustment Mechanisms - Goldfeld, Stephen M.; Sichel, Daniel E. (The Review of Economics and Statistics, 1987)
The paper first reconciles a variety of specification tests for partial adjustment money demand models and points out a fundamental identification problem which makes it impossible to distinguish between the real and nominal partial adjustment models if inflation has an independent effect on the long-run demand for money. The paper also finds that empirical estimates of simple partial adjustment models have some undesirable properties and then considers the shortand long-run effects of inflation in a more general distributed lag model.